Kikuchi–Fujimoto Disease: A Case Series and Review of the Literature - Arunima Deb; Vielka Fernandez; Ekim Kilinc; Hisham F. Bahmad; Nicholas S. Camps; Vathany Sriganeshan; Ana Maria Medina (Diseases)
Kikuchi–Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, is a rare, self-limiting disorder characterized by fever typically lasting for 1 week up to 1 month and painful necrotizing lymphadenopathy, primarily affecting young adults of Asian ancestry. Although the exact cause remains unclear, infectious and autoimmune mechanisms have been implicated in the pathogenesis of the disease. In this case series, we aim to describe the histopathological features of KFD over a ten-year period at Mount Sinai Medical Center of Florida, and review the current understanding of its pathogenesis, clinical presentation, diagnosis, and management. A retrospective review of our pathology database between January 2013 and May 2024 was performed to identify patients diagnosed with KFD at our institution. Eight cases of KFD were identified, with a mean age of 35 years (range 24–49) and slight male predilection (5:3). Three patients exhibited leukopenia, and two had concurrent HIV infection. One patient developed systemic lupus erythematosus (SLE), and another developed IgA nephropathy during follow-up. Histopathological examination revealed the characteristic features of KFD, including lymph node architectural effacement, histiocytic infiltration, and necrosis. In conclusion, KFD remains a diagnostic challenge due to its overlapping clinical features with other infectious and autoimmune diseases, particularly SLE. While most cases resolve spontaneously, long-term follow-up is warranted due to the potential for recurrence and autoimmune associations.